THE RIGHT TO BE HUMAN AND THE CHALLENGES OF ITS IMPLEMENTATION: FROM HISTORICAL ORIGINS TO THE PRESENT - Cherevatyuk, Victoria; Temchenko, Yana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Рurpose: the article explores the problematic aspects of the right to be human and its implementation from historical origins to the present day. Research methods: to achieve the defined goal, general and special scientific (specialized) methods were used, including dialectical, historical, structural-functional, comparative, logical-legal methods, and others. Results: the historical development of the right to be human has been examined, from antiquity, through medieval and Renaissance ideas, to modern approaches. The contributions of thinkers such as Socrates, Plato, Aristotle, Thomas Aquinas, and Erasmus of Rotterdam to the formation of the idea of understanding the right to be human have been considered. Contemporary challenges that hinder the realization of the right to be human have been analyzed, including digitalization, privacy violations, discrimination, and military conflicts. A wide range of factors—social-political, economic, and cultural-impede individuals from fully exercising their diverse rights, primarily due to their complexity. Discussion: with the right to be human comes the obligation to respect the rights of others. This means not only refraining from actions that harm others but also actively working towards the creation of a society where everyone’s rights are upheld. It implies responsibility for one’s actions and a contribution to the common good. The proper realization of the right to be human requires coordinated efforts at all levels: local, national, and international. Solving issues related to the realization of the right to life necessitates adherence to equality, justice, and respect for all people, regardless of their background. There is an urgent need today for the development of a global culture that values human dignity and actively works to protect and uphold human rights for all.